Post-colostomy internal hernia of the stomach treated with laparoscopic gastropexy: a case report - Yoichiro Tada; Junpei Orihara; Yamato Wada; Ei Uchinaka; Tomohiro Osaki; Keigo Ashida; Shigeru Tatebe; Seika Kuroda; Yasuaki Hirooka (Surgical Case Reports)
Abstract Background Internal hernias are formed by the protrusion of internal organs through an aperture formed congenitally or postoperatively. Internal hernias are most commonly associated with the small intestine. Only two cases of a post-sigmoid colostomy internal hernia of the stomach have been reported. This hernia arises from the space between the lifted sigmoid colon and the left abdominal wall. In the two aforementioned cases, treatment comprised suturing of the sigmoid colon to the lateral abdominal wall and changing of the intraperitoneal route to an extraperitoneal one. Herein, we present a very rare case who underwent laparoscopic gastropexy for a post-sigmoid colostomy internal hernia of the stomach. Case presentation Our patient, a 67-year-old woman, was undergoing chemoradiation for rectal cancer and planned to undergo abdominoperineal resection. However, tumor perforation resulted in a high fever and a right gluteal abscess; therefore, a sigmoid colostomy was performed through the intraperitoneal route in the left lower abdomen. One month after the surgery, the patient presented to our emergency room with vomiting, abdominal pain, and abdominal distension. Computed tomography revealed a markedly distended stomach caused by the obstruction of the pylorus secondary to the colostomy; laparoscopic gastropexy was performed subsequently and the postoperative course was uneventful. Conclusions This is the first report on the laparoscopic gastropexy treatment of a post-sigmoid colostomy internal hernia of the stomach; our findings may help physicians manage such hernias.